Perancangan Aplikasi Unggah Informasi Kecelakaan dari Masyarakat Berbasis Android di PT. Jasa Raharja - Aji, Bondan Sasmito; Saian, Pratyaksa Ocsa Nugraha (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
PT. Jasa Raharja is a state-owned company engaged in accident insurance services, located in Kuningan, south of Jakarta. At this time, PT. Jasa Raharja does not yet have an accident information application to monitor traffic conditions. Of course, technological developments have made it possible for the agency to have an accident information application while at the same time being able to find out the location of the accident. Based on the existing problems, this research was conducted to find a solution to the existing problem by designing an accident information application that can report accidents through Android-based communities using Java. This study applies the waterfall method with the stages of requirement, design, implementation, verification, and maintenance. Based on the test results for prospective users using a Likert scale, it obtained a value of 85.2% with statements that strongly agreed. Through the acquisition of the Likert scale value, it means that the application designed can help the public distribute information on accidents that have occurred and can satisfy potential users of the application